Self-Care Habits of Undergraduate Nursing Students at University of Lahore - Javed, Anita; Mukhtar, Sunil; Majeed, Iram; Afzal, Mohammad; Gilani, Syed Amir (International Journal of Social Sciences and Management, 2019)
Self-care is a dynamic decision to take an interest in the activities that are known to build general physical, emotional, mental, social, spiritual well-being, improving inspiration, struggle for ideal wellbeing with support to change the way of life to move toward a condition of ideal wellbeing. Cross-sectional descriptive research design was used to conduct the study. Sample (n=133) was taken from nursing institutes by using convenient sampling. 5 point Likert scale base self-administered questionnaire was used for the collection of data. Data was analyzed by using SPSS version 21. Ethical clearance was obtained before research. One sample T test was applied. Nursing students have positive self-care habits as P value regarding self-care habits is significance (p=.000). The study of self-care practices is an important component of health promotion and disease prevention . Students have positive self-care habits related to health.It is clear stated that nursing students have adequate knowledge about self-care habits.